On Being Difficult: The Pursuit of Wonder - Kareem, Sarah (Lumen, 2020)
Is discomfort intrinsic to wonder? The author pursues this question by showing how early visitors to the Niagara Falls found that efforts to improve the view eliminated the difficulty that made viewing the falls rewarding in the first place. Visitors’ experiences accord with eighteenth-century accounts that suggest that wonder thrives on difficulty and desire thrives on inaccessibility. This aesthetic effect finds expression in The Arabian Nights and other texts that both represent and enact narrative withholding, and also in the visual form of the arabesque, which beguiles the eye with movement but does not go anywhere. The essay concludes by connecting these insights into aesthetic difficulty to present-day concerns that attempts to bring the humanities to a broader audience may “dumb down” art. I conclude that such concerns miss the point that aesthetic experiences depend upon a tension between legibility and illegibility that artworks continue to generate in new and unforeseen ways.